Transformation of Personal Spirituality through Digital Technology: A Systematic Literature Review - Gerardette Philips (Parahyangan Catholic University, 2025)
This study aims to analyse how the experience of “loving God” as a form of personal spirituality undergoes transformation in the digital age, in which religion and technology increasingly intersect in everyday life. The urgency of this research arises from the reality that digital media has become an integral part of religious practice, reshaping the ways individuals pray, meditate, and build communities of faith. This study employs a Systematic Literature Review (SLR) of journal articles, books, dissertations, and research reports published between 2015 and 2025. The data collection process follows the PRISMA protocol, while the analysis proceeds through stages of coding, categorisation, and narrative synthesis of emergent themes. Data sources are drawn from Scopus, Web of Science, Google Scholar, and ProQuest. The analysis focuses on three key dimensions: (1) the transformation of spiritual practices, (2) the ambiguity of religious identity and authority in cyberspace, and (3) the dual role of technology as both a means of reinforcing and commodifying faith. The findings indicate that personal spirituality in the digital age is hybrid and interactive. Digital platforms facilitate broader access to prayer, meditation, and interfaith dialogue, yet simultaneously blur the boundaries of religious identity and authority. Technology strengthens faith through new forms of spiritual connectivity, while also transforming faith into a commodity shaped by algorithmic and market logics. This hybrid spirituality is characterised by continuous connectedness, negotiated religious identities, faith experiences constructed as content, and a tendency to transcend the limits of institutional traditions. The implications of this study include the strengthening of digital religious education, the development of ethical guidelines for the use of technology in spiritual contexts, and the formulation of governance policies for online religious content that respond more reflectively to contemporary dynamics of faith. The originality of this research lies in constructing a conceptual framework of hybrid spirituality, synthesising previous literature into a new analytical model that explains how technology not only mediates but also transforms the experience of loving God in the digital age.